The Procoagulant and Fibrinolytic Balance of Extracellular Vesicles Predicts Mortality in Septic Shock Patients - Romaric Lacroix; Coralie Judicone; Karim Harti Souab; Amandine Bonifay; Anderson Loundou; Tarik Bouriche; Sylvie Cointe; Loris Vallier; Evelyne Abdili; Laurent Arnaud; Stéphane Robert; Philippe Poncelet; et al. (Journal of Extracellular Vesicles)
ABSTRACT Septic shock is characterised by abnormal coagulation activation with defective fibrinolysis, leading to a high mortality rate. Cellular activation triggers the release of extracellular vesicles (EVs) conveying both procoagulant and fibrinolytic activities. We investigated whether the balance between these activities, termed EV‐coagulolytic balance (EV‐CLB), predicts day‐90 mortality in 225 septic shock patients included in a multicentre prospective study. EV‐CLB, quantified as a ratio of TF‐dependent thrombin generation to uPA‐dependent plasmin generation, was higher in non‐survivors than in survivors at 24 h (2.78 [0.86–16.1] a.u. vs. 0.97 [0.34–2.18] a.u., p < 0.001). Moreover, survivors showed a significant decrease in EV‐CLB from H0 to H48 in contrast to non‐survivors. EV‐CLB was a better predictor than EV‐associated–procoagulant and ‐fibrinolytic activities taken individually and better correlated with sepsis severity markers such as SAPS II and lactate levels. Multivariate Cox regression models including severity markers and comorbidities confirmed EV‐CLB as an independent predictor of mortality in septic shock patients. Interestingly, subgroup analysis revealed EV‐CLB's strong prognostic value in peritonitis, biliary and urinary tract infections and Gram‐negative sepsis. Despite challenges in EV measurement requiring technical advancement for clinical translation, EV‐CLB represents a potential novel biomarker to guide individualised therapy targeting coagulation/fibrinolysis imbalance in septic shock. Trial Registration: This trial was registered at ClinicalTrials.gov identifier: NCT02062970